Video Pembelajaran Berbasis Model Discovery Learning pada Muatan IPS Kelas IV Sekolah Dasar - Ni Komang Ayu Suci Lestari; I Wayan Sujana (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
The limitation of teachers in finding the right learning media in learning situations in the network is a problem in the learning process. The purpose of this research is to produce a product in the form of a discovery learning-based learning video that is feasible to use. The research model used is the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Data collection methods used are interviews and questionnaires. The product design test was carried out by several experts and students including (1) content experts, (2) learning design experts, (3) learning media experts, and (4) individual trials consisting of three students. The data analysis method used is quantitative and qualitative descriptive data analysis. Based on the research data, the percentage level of feasibility of learning videos according to content experts is 93,75% with very good qualifications, the percentage level of feasibility of learning videos according to learning design experts is 90,38% with very good qualifications, and the feasibility level of learning videos according to media experts learning by 87,5% with good qualifications and according to individual trials the percentage level of eligibility for learning videos is 91,66% with very good qualifications. Based on the results of the study, it can be concluded that the development of learning videos based on the discovery learning model is feasible to use in the learning process on social studies content for fourth-grade students in elementary schools.